Production of isotopes ¹⁸⁴Re, ¹⁸⁶Re and ¹⁸⁸Re at linear electron accelerators of NSC KIPT - Dovbnya, A.N.; Dikii, N.P.; Zadvornyi, A.S.; Kovtun, G.P.; Torgovkin, A.V.; Shramenko, B.I. (Вопросы атомной науки и техники, 2001)
This paper presents the preliminary results on determining the values of specific activity of radionuclides ¹⁸⁴Re, ¹⁸⁶Re and ¹⁸⁸Re. Irradiation of Re targets of a natural isotope composition with gamma-quanta and neutrons was conducted at NSC KIPT linear accelerators. Possible levels of activity of the above-mentioned radionuclides are forecasted.